Effect of ascent to a moderate altitude on muscle power: normobaric hypoxia vs hipobaric hypoxia - Feriche, B.; Calderon-Soto, C.; Chirosa, I.; Chirosa, L. J.; Escobar, R.; Olea, F.; Mariscal, M.; Bonitch-Gongora, J.; Bonitch, J.; Galilea, P.; Riera, J.; Gutierrez, J. A.; et al. (Archivos de medicina del deporte, 2008)
The main objective of this study is to analyze the effect of changes in barometric pressure and/or air composition on muscular power in different levels of loads. To study this objective, two groups of male wrestlers, competing at national and international levels, took part in this research. One group executed the protocol under normoxia (N1) and breathing mixed gas at 15.7%FIO2 (NH) in the CAR of Sant Cugat at sea level. The other did it under N (N2) and after a sudden ascent to a moderate altitude (CAR of Sierra Nevada, 2320m, HH). The protocol consisted of a test of increasing loads (F-V curve) in the bench-press (concentric phase), determining the power (P), force (F), and velocity (V), with an electronic dynamometer (Real power Pro of Globus), at different loads and the variables related to the maximum power (MP). The results show no FIO2 effect in the MP (414.50 ±99.03 vs 407.17±84.92 W to N1 and NH), the variables analyzed on it and in the F-V curve between N1 and NH (P>0.05). The change in barometric pressure displays similar MP between conditions (481.50 ±99.80 vs 464.36 ±89.87 W for N2 and HH) although they were obtained at the highest loads (46.64 ±11.2 vs 51.82 ±14.01 Kg for N2 and HH, P=0.034). This group presents a F-V curve significantly favoured by HH in the power zone, showing an average increase of 5.92± 4.54%; 7.37 ±1.55% and 1.04 0.33% of P, V and F respectively (P<0.05). We can conclude that the changes in the air density with the ascent led to a 20% load increase to achieve MP similar to sea level. Acute moderate altitude improves the capacity to perform actions at high velocity and, makes training at moderate altitude an ideal complement to achieve peak performance in the technical components in power-explosive sports.